MODELING COMMUTER PREFERENCES FOR A BUS - Nyarko, Eric; Owusu-Ansah, Caleb; Kwofie, Charles (European Scientific Journal, ESJ, 2015)
The research deals with the use of the discrete choice experiment technique and Random Utility Theory (RUT) to analyze bus choice behaviour for commuters in Asafo-market in Kumasi, Ghana. The principal aim of the study was the calibration of a logit model to forecast consideration sets. In order to estimate the model parameters, a specific survey was carried out inside the urban area of Kumasi. The survey focused on passengers and involved mainly employees, self employed workers and students (120 respondents). The data collected from the experimental survey was further calibrated and segmented according to gender. The magnitude of estimates generally indicates that commuters highly value buses with fixed departure time, spacious seats and Air Condition (AC). However, an increase in fare level will result in a disutility of bus choice.